Pengaruh Kinerja Aparat Penegak Hukum Terhadap Tingkat Efektivitas Penegakan Hak Asasi Manusia Dalam Menangani Kasus Perdagangan Orang - Yurika Sakinah Sakinah; Rahma Adzkia Putri; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Human trafficking is a serious violation of human rights because it harms the dignity, freedom, and safety of the victims. The main issue in dealing with human trafficking crimes in Indonesia is the effectiveness of law enforcement agencies, which often face obstacles from both structural and cultural factors. This paper aims to analyze how well the legal institutions perform in protecting victims' rights, identify the challenges faced, and develop strategies to improve the effectiveness of legal enforcement. The research method used is normative legal analysis with a legislative and conceptual approach. This study reviews various national legal instruments, such as Law Number 39 of 1999 on Human Rights and Law Number 21 of 2007 on the Eradication of Human Trafficking Crimes, as well as international instruments that have been ratified by Indonesia. The findings show that the role of law enforcement agencies is crucial in the success of enforcing human rights, whether in the functions of repression, prevention, or rehabilitation. However, there are still challenges such as limited resources, lack of coordination between agencies, corruption practices, and low understanding of human rights principles among law enforcement. Therefore, a comprehensive strategy is needed through strengthening the capacity of law enforcement, using modern investigation technologies, improving cooperation between national and international agencies, and ensuring victim-centered recovery.